THE INFLUENCE OF LEARNING STRATEGIES AND SELF-RELIANCE ON PPKN LEARNING OUTCOMES IN FIFTH GRADE AT SDN 060931 MEDAN - Putri Indaayu; Reh Bungana Br. Perangin-angin; Daulat Saragi (Jurnal Ilmiah Teunuleh, 2021)
This study aims to: knowing the difference the result of learning PPKn students taught with the learning strategy problem-based learning and concept map of learning strategies, knowing the difference result of learning PPKn students who have learning independence high with students who have learning independence is low, determine the interaction between learning strategies and self-regulated learning is affecting the learning outcomes PPKn. This research is experimental research. The population in this research is all students of class V SD Negeri No. 060931 Medan academic year 2020/2021 which consists of two classes. The sample selected by total sampling technique. The instrument used is the questionnaire of independence in student learning and tests the learning outcomes of students. Data obtained from the research instrument were then analyzed using two-way ANAVA on SPSS 23.0 for Windows. The results showed that: There is a significant difference between the result of learning PPKn students taught with the learning strategy of problem-based learning compared with the learning strategies concept map (Fcount = 23,476 and the value of sig. 0,000 < 0,05), the result of learning PPKn students who have learning independence higher compared with students who have to learn independence low (Fcount = 7,673 and the value of sig. Are 0.008 < 0.05), and there is an interaction between learning strategy and self-regulated learning in influencing the result of learning PPKn students (Fcount = 13,003 and the value of sig. 0,001 < 0,05).